2021
DOI: 10.1037/men0000271
|View full text |Cite
|
Sign up to set email alerts
|

Self-compassion and body dissatisfaction in men: Extension of the tripartite influence model.

Abstract: Self-compassion, an increasingly popular psychological construct, has been associated with masculine norm adherence, shame, and rumination. However, limited research has considered the relationship between self-compassion and body image; a construct that heavily overlaps with masculinity for men in contemporary Western culture. This study examined the relationship between self-compassion, body dissatisfaction, and sociocultural processes (social comparison, internalization of appearance ideals) in 231 Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Although significant improvements in self-compassion were found for male participants after the intervention, the effect was weaker, and not significant at follow-up. As self-compassion has been identified as a crucial factor in reducing body dissatisfaction and enhancing body appreciation in female and male participants [ 29 , 73 , 74 ], the weaker effects observed for self-compassion in male participants may have had a downstream effect and explained the lack of follow-up effects for male participants’ body dissatisfaction and body appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant improvements in self-compassion were found for male participants after the intervention, the effect was weaker, and not significant at follow-up. As self-compassion has been identified as a crucial factor in reducing body dissatisfaction and enhancing body appreciation in female and male participants [ 29 , 73 , 74 ], the weaker effects observed for self-compassion in male participants may have had a downstream effect and explained the lack of follow-up effects for male participants’ body dissatisfaction and body appreciation.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a community sample of women, the relation between external shame and drive for thinness was partially mediated by self-compassion, and the relation between body dissatisfaction and drive for thinness was not mediated by self-compassion. In a recent study of men, Maher et al (2021) found that high levels of self-compassion predicted lower levels of body dissatisfaction, and that self-compassion moderated the relation between appearance ideal internalization and body dissatisfaction such that appearance ideal internalization and body dissatisfaction were more strongly associated when self-compassion was low. Cross-sectional research has also shown that individuals with clinical eating disorders such as anorexia nervosa and bulimia nervosa have lower levels of self-compassion and higher levels of fear of self-compassion compared to non-clinical samples (e.g., Kelly et al, 2014b).…”
Section: Cross-sectional Studiesmentioning
confidence: 98%
“…Sociocultural frameworks has the past decade also been used to explain muscle-oriented body image and muscle building behaviors ( Rodgers et al, 2012 , 2020 ; Girard et al, 2018a , b ; Carvalho and Ferreira, 2020 ). The sociocultural theories of body image, ED symptomatology, and muscle building behaviors have been tested and modeled in cross sectional and longitudinal studies ( Rodgers et al, 2011 , 2012 , 2014 , 2015 ; Girard et al, 2018a , b ; Carvalho and Ferreira, 2020 ; Burke et al, 2021 ; Maher et al, 2021 ; Schaefer et al, 2021 ). In summary, these studies suggest that perceived appearance pressure from sociocultural sources (e.g., media, family, and peers) explains body image, ED symptomatology, and muscle building behaviors through mechanisms of appearance internalization and social comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one study, and among girls only, has included self-esteem as a potential mediator for intervention effect ( Agam-Bitton et al, 2018 ). Moreover, self-compassion and body image flexibility act as moderators between appearance internalization and social comparison and ED symptomatology ( Perey and Koenigstorfer, 2020 ; Maher et al, 2021 ). This indicates that the risk of ED development caused by appearance internalization and social comparison may be outnumbered by body image flexibility and self-compassion.…”
Section: Introductionmentioning
confidence: 99%